Simulation as a means to develop firefighters as emergency care professionals. Issue 4 (2nd October 2019) - Abelsson, Anna; Lundberg, Lars
Abstract : Objective . The aim of this study was to evaluate the simulated emergency care performed by firefighters and their perception of simulation as an educational method. Methods . This study had a mixed method with both a quantitative and a qualitative approach. Data were collected by simulation assessment, a questionnaire and written comments. Descriptive analysis was conducted on the quantitative data whereas a qualitative content analysis was conducted on the qualitative data. Finally, a contingent analysis was used where a synthesis configured both the quantitative and the qualitative results into a narrative result. Results . The cognitive workload that firefighters face during simulated emergency care is crucial for learning. In this study, the severity and complexity of the scenarios provided were higher than expected by the firefighters. Clearly stated conditions for the simulation and constructive feedback were considered positive for learning. Patient actors induced realism in the scenario, increasing the experience of stress, in comparison to a manikin. Conclusion . Simulation in a realistic on-scene environment increases firefighters' cognitive ability to critically analyze problems and manage emergency care. Simulation of emergency care developed the firefighters as professionals.